589. Oral Tablet Vaccination Induces Heightened Cross-Reactive CD8 T Cell Responses to SARS-COV-2 in Humans. (4th December 2021) - Johnson, Susan; Martinez, Clarissa; Cortese, Mario; Martinez, Josefina; Garg, Shaily; Peinovich, Nadine; Dora, Emery; Tucker, Sean
Abstract: Background: Covid-19 has accelerated global demand for easily distributed vaccines. Furthermore, as variant SARS-CoV-2 strains that circumvent antibody responses emerge, cross-protective vaccines provide substantial public health benefits. Vaxart is developing a shelf stable oral tablet vaccine that incorporates both the spike (S) and the more conserved nucleocapsid (N) proteins. Vaxart's vaccine platform uses a non-replicating adenovirus and a TLR3 agonist as an adjuvant. Methods: In an open-label phase 1 clinical study, 35 healthy subjects received either a single low (1x10 10 IU; n=15) or high (5x10 10 IU; n=15) dose of the vaccine candidate VXA-CoV2-1 with a small cohort receiving 2 low doses. PBMCs were taken at pre- and 7 days post-vaccination and restimulated with S and N peptides from SARS-CoV-2 or the 4 human endemic coronaviruses (HCoV). Cells were stained for CD4/CD8/CD107a (surface) and IFNγ/TNFα (intracellular). Subjects that received an intramuscular (i.m.) mRNA vaccine had PBMCs taken at the same timepoints and were compared in the same assay. Results: The study's results indicate that the VXA-CoV2-1 tablet was well tolerated. The majority of subjects had an increase in S-specific anti-viral CD8 + T cell responses. 19/26 (73%) subjects had a measurable CD8 + T cell response on day 8 above baseline, on average 1.5-4.6%. In a comparator experiment with the 2 SARS-CoV-2 i.m. mRNA vaccines, VXA-CoV2-1 outperformed other vaccine candidates with a >3.5-fold increase in S specific antiviral CD8 T cell responses. T cell responses specific to the 4 endemic HCoV were increased by 0.6% in subjects given VXA-CoV2-1. Conclusion: Here we describe a room temperature stable tablet that induces SARS-CoV-2 S specific CD8 T cells of high magnitude after one dose in humans. Overall, the level of antiviral SARS-CoV-2 specific T cells, particularly IFNg-producing CD8s, induced following oral immunization with VXA-CoV2-1 are of higher magnitude than the mRNA vaccines currently in use against COVID-19. T cell responses against 4 endemic HCoV were also induced. Because T cells may be important in protecting against death and severe infection, these results suggest that VXA-CoV2-1 could be cross-protective against a wide array of emerging pandemic coronaviruses. Disclosures: Susan Johnson, PhD, Vaxart (Employee) Clarissa Martinez, MPH, Vaxart (Employee) Mario Cortese, PhD, Vaxart (Employee) Josefina Martinez, n/a, Vaxart (Employee) Shaily Garg, BS, Vaxart (Employee) Nadine Peinovich, MPH, Vaxart (Employee) Emery Dora, n/a, Vaxart (Employee) Sean Tucker, PhD, Vaxart (Employee)